Responding to Climate Change: Participatory Evaluation of Adaptation Options for Key Marine Fisheries in Australia’s South East - Ogier, Emily; Jennings, Sarah; Fowler, Anthony; Frusher, Stewart; Gardner, Caleb; Hamer, Paul; Hobday, Alistair J.; Linanne, Adrian; Mayfield, Stephan; Mundy, Craig; Sullivan, Andrew; Tuck, Geoff; et al. (Frontiers in Marine Science, 2020)
Planned adaptation to climate impacts and subsequent vulnerabilities will necessarily interact with autonomous responses enabled within existing fisheries management processes and initiated by the harvest and post-harvest components of fishing industries. Optimal adaptation options are those which enable negative effects to be mitigated and opportunities that arise to be maximised, both in relation to specific climate-driven changes and the broader fisheries system. We developed a two-step participatory approach to evaluating adaption options for key fisheries in the fast-warming hotspot of south-eastern Australia. Four fisheries (southern rock lobster, abalone, snapper and blue grenadier) were selected as case studies on the basis of their high to moderate vulnerability to climatic effects on species distribution and abundance. Involved stakeholders undertook a “first pass” screening assessment of options, by characterising and then evaluating options. In the characterisation step potential adaptation options for each fishery, contextualised by prior knowledge of each species’ climate change exposure and sensitivity, were described using a characterisation matrix. This matrix included: the specific climate vulnerability/challenges, the implications of each option on the fishery system as a whole, the temporal and spatial scales of implementation processes, and realised benefits and costs. In the evaluation step, semi-quantitative evaluation of options was undertaken by stakeholders scoring the anticipated performance of an option against a pre-determined set of criteria relating to perceived feasibility, risk (inclusive of potential costs) and benefit. Our screening assessment represents a pragmatic approach to evaluate and compare support for and the effects of alternative adaptation options prior to committing to more detailed formal and resource intensive evaluation or implementation.